The Space of Persistence Diagrams Fails to Have Yu’s Property A - Bell, Greg; Lawson, Austin; Pritchard, Neil; Yasaki, Dan (Topology Proceedings, 2021)
We define a simple obstruction to Yu’s property A that we call k-prisms. This structure allows for a straightforward proof that the space of persistence diagrams fails to have property A in a Wasserstein metric.